OPTIMALKAN KESEHATAN MASYARAKAT: SOSIALISASI SWAMEDIKASI KOMPREHENSIF HIPERTENSI MELALUI PENGOBATAN TRADISIONAL PADA MASYARAKAT RT 03 DUSUN KEDON DESA REJOSARI - Soraya, Devinta Febri; Abdillah, Salma Iliyina; Widiyanto, Andi; Rizal, Mar'ie Muhammad; Yulina, Rayung Putri (Prosiding University Research Colloquium, 2024)
Self- medication is an effort to self- medicate, the implementation of which involvesrecognizing the symptoms of a disease and selecting the medication on one's own initiativewithout going to a doctor or other health worker. Hypertension is a health problem that isquite dangerous throughout the world because hypertension is the main risk factor thatleads to cardiovascular disease such as heart attack, heart failure, stroke and kidneydisease. Alternative medicine or preventative measures are conventional medicine. Theuse of traditional medicine, especially plants, to improve public health is increasinglywidespread. The use of medicinal plants, either alone or in combination, has long beenused to reduce the symptoms of high blood pressure. Medicinal plants that are known tolower blood pressure include celery leaves and cat's whisker leaves. Both plants containcompounds that can help prevent high blood pressure. The aim of this activity is to increasep ublic awareness of the importance of maintaining normal blood pressure and to find outthe effect of giving traditional plant preparations which can be used as antihypertensiveson the blood pressure of residents of RT 3 Bandongan District who experienceh ypertension